2004
DOI: 10.1016/s0021-9797(04)00380-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent labels to study thermal transitions in epoxy/silica composites

Abstract: The analysis of the fluorescen response from the dansyl moiety as a function of temperature has been used to estimate the thermal transi-tions in silica particle/epoxy-based composite materials. Silica particles were surface-coated with 3-aminopropyltriethoxysilane (APTES) and 3-aminopropylmethyldiethoxysilane (APDES). 5-Dimethylamino-1-naphtalenesulfonyl chloride (DNS) and 5-dimethylaminonaphthalene-1-(2-aminoehyl)) sulfonamide (DNS-EDA) were selectively attached to the silanized silica particles and to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A small amount of dansyl chloride (DNS-Cl) was dissolved and stirred in 2 mL of a specific silane. The sulfonyl group of DNS-Cl easily reacts with amines [33,35,36] to form the fluorescent sulfonamide derivative (DNSA). The reactant ratio was 1:1000 (dansyl:NH 2 ) ensuring the small amount of fluorophore, required to assume no alteration of the final properties of glass fibre silane coating.…”
Section: Surface Modification Of the Glass Fibresmentioning
confidence: 99%
See 1 more Smart Citation
“…A small amount of dansyl chloride (DNS-Cl) was dissolved and stirred in 2 mL of a specific silane. The sulfonyl group of DNS-Cl easily reacts with amines [33,35,36] to form the fluorescent sulfonamide derivative (DNSA). The reactant ratio was 1:1000 (dansyl:NH 2 ) ensuring the small amount of fluorophore, required to assume no alteration of the final properties of glass fibre silane coating.…”
Section: Surface Modification Of the Glass Fibresmentioning
confidence: 99%
“…The advantage of using such a small amount of emissive moieties is that no perturbation is introduced in the system. In general, the fluorescence emission changes when polarity and/or rigidity variations occur in the system where the fluorophore is immersed [33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…One way to analyze the contribution at longer wavelengths when there are BaTiO 3 particles within the PS is to use the so called first moment of the emission band, on 4, [1][2][3][4]7,8,10] which represents the average energy of the light emitted:…”
Section: Resultsmentioning
confidence: 99%
“…Several studies about polymeric systems have revealed a sharp change in the tendency of the fluorescence intensity of fluorescent probes at a certain temperature [3,10]. These phenomena can be understood by considering the following equation where quenching phenomena and chemical reactions are considered negligible:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation